Comparative effectiveness of different exercise modality on glycaemic control and lipid profile for prediabetes: systematic review and network meta-analysis - Yan, Ruixiang; Chen, Lunxin; Lin, Gesheng; Shi, Yuer; Huang, Wenrui; Mai, Yuqiang; Sun, Jian; Li, Duanying (Frontiers in Endocrinology, 2025)
BackgroundPrediabetes is the precursor to type 2 diabetes and represents a critical, reversible window for intervention. This study aims to systematically review and conduct a network meta-analysis to evaluate the efficacy of aerobic training (AT), resistance training (RT), combined training (AT+RT), high-intensity interval training (HIIT), and traditional Chinese exercises (TCEs) on glycemic control, lipid profile, and weight management in prediabetic individuals. This marks the first time HIIT and TCEs have been included in such an assessment.MethodsA systematic search was conducted across PubMed, Web of Science, Cochrane (CENTRAL), Embase, CNKI, and WangFang Data for randomized controlled trials (RCTs) on the effects of different exercise modalities on prediabetic patients published up to August 10, 2024. Network meta-analysis was performed using the “gemtc” package in R software, and the quality of evidence was assessed using the CINeMA framework.ResultsA total of 74 studies involving 5,683 participants were included. The network meta-analysis results showed that HIIT was the most effective for reducing haemoglobin A1c (HbA1c) (-0.44%, 95% CI: -0.55% to -0.32%, SUCRA 93.8%), 2-hour plasma glucose (2hPG) (-1.3, 95% CI: -1.6 to -0.93, SUCRA 84.3%), and increasing high-density lipoprotein (HDL) (0.20, 95% CI: 0.03 to 0.36, SUCRA 87.3%). AT+RT was most effective in reducing total cholesterol (TC) (-0.46, 95% CI: -0.61 to -0.32, SUCRA 98.3%), TG (-0.55, 95% CI: -0.69 to -0.42, SUCRA 99.9%), low-density lipoprotein (LDL) (-0.35, 95% CI: -0.53 to -0.18, SUCRA 82.2%), and body mass index (BMI) (-0.89, 95% CI: -1.6 to -0.14, SUCRA 66.4%). TCEs showed the most significant improvements in reducing 2hPG (-1.3, 95% CI: -1.5 to -1.0, SUCRA 83.5%), body weight (BW) (-3.4, 95% CI: -6.4 to -0.51, SUCRA 79.1%), and wasit circumference (WC) (-4.27, 95% CI: -7.53 to -0.98, SUCRA 84.6%).ConclusionVarious exercise interventions significantly improved glycemic and lipid profiles in prediabetic patients. HIIT and AT+RT were found to be the most effective interventions. For elderly individuals with limited physical activity or chronic conditions, TCEs can serve as a gentle and safe alternative. These findings provide the latest evidence to support exercise interventions for managing prediabetes.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024578405.